Implications of high throughput sequencing of plant viruses in biosecurity – a decade of progress? - Fox, A.; Botermans, M.; Ziebell, H.; Fowkes, A.R.; Fontdevila, N.; Massart, S.; Rodoni, B.; Chooi, K.M.; Kreuze, J.; Kumar, P.L.; Cuellar, W.J.; Carvajal-Yepes, M.; et al. (Association of Applied Biologists Virology Group, 2025)
In the 15 years since High Throughput Sequencing (HTS) was first used for the detection and identification of plant viruses, the technology has matured and is now being used in frontline plant biosecurity applications. Anticipating the challenges this new approach was starting to reveal, recommendations were made a decade ago to streamline the application of these technologies (MacDiarmid et al., 2013). The recommendations were (1) for countries to increase baseline surveillance, (2) to address nomenclature for “data inferred” new viral sequence to differentiate from characterised viruses, and (3) to increase the focus on fundamental biological research to deal with the deluge of new virus discoveries. The progress made on these recommendations in the intervening decade has been as much about changing philosophical approaches as about advancing practical research. As we move towards a potential asymptote in the rate of virus discovery, the anticipated future challenges posed by the broader adoption of HTS in routine biosecurity applications need to be considered. In addition to these three recommendations, which remain relevant, a fourth recommendation is becoming necessary: (4) to ensure equal inclusion and access to research and technology, both locally and globally, with a particular emphasis on countries in the global south. The potential impact of these recommendations on researchers, risk analysts, biosecurity authorities, and policymakers at national and international levels to achieve a reduction of biosecurity incursions of phytopathogenic viruses will be discussed.